The Correlation Between Students’ Higher Order Thinking Skills and Their English Achievement at Seventh Grade - Dila Azhani; Reflinda Reflinda; Hilma Pami Putri; Veni Roza (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
The background of this research was that there were several problems regarding students' English achievement and their higher order thinking skills. Theory said that higher order thinking skills can be a tool that can help improve student learning achievement. Researchers found there was a difference between theory and facts in the field. Teachers have implemented HOTS in the learning process, but English scores are still low. Therefore, researchers want to know the relationship between students' HOTS and their English achievement. The design of this research is correlational research. Researchers used test instrument to collect students' HOTS scores, and documentation was used to collect students' English scores in their second semester report cards. The population of this research was all seventh grade students, which consist two classes. The sample of this research was class VII A, totaling 24 students. The sampling for this research was cluster sampling. Researchers used Bivariate Pearson Correlation to determine the correlation between the two variables. The results of this research showed that the correlation coefficient between the two variables is 0.471. Then the magnitude of the correlation is sufficient, around 0.40-0.60. Thus, there is a positive correlation between students' higher order thinking skills (HOTS) and their English achievement in the seventh grade of SMPN 3 Koto Besar.